2006
DOI: 10.1115/1.1805548
|View full text |Cite
|
Sign up to set email alerts
|

Study of High Load Operation Limit Expansion for Gasoline Compression Ignition Engines

Abstract: In this research, combustion characteristics of gasoline compression ignition engines have been analyzed numerically and experimentally with the aim of expanding the high load operation limit. The mechanism limiting high load operation under homogeneous charge compression ignition (HCCI) combustion was clarified. It was confirmed that retarding the combustion timing from top dead center (TDC) is an effective way to prevent knocking. However, with retarded combustion, combustion timing is substantially influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Although delaying the spark timing could achieve lower PRR max for the Flat Piston, the IMEP decreased more significantly. In addition, the delaying of the combustion phasing could lead to unstable combustion [17,24]. Piston C shows the latest CA50 and lowest IMEP among all pistons though its PRR max is not the lowest.…”
Section: Effect Of Piston Shapesmentioning
confidence: 95%
See 1 more Smart Citation
“…Although delaying the spark timing could achieve lower PRR max for the Flat Piston, the IMEP decreased more significantly. In addition, the delaying of the combustion phasing could lead to unstable combustion [17,24]. Piston C shows the latest CA50 and lowest IMEP among all pistons though its PRR max is not the lowest.…”
Section: Effect Of Piston Shapesmentioning
confidence: 95%
“…In terms of the SI-CAI hybrid combustion, the fuel stratification was also proposed to evaluate its potential to extend the high load limit. Yoshizawa et al [24] developed a two-step combustion concept to expand the high load operation in a gasoline compression ignition engine. In this two-step combustion concept, the spark plug would be used only for igniting a small quantity of a fuel rich mixture at the bore centre and the remaining fuel would be ignited by auto-ignition.…”
Section: Introductionmentioning
confidence: 99%
“…One of the challenges facing their further implementation is the limited load range in which they operate. Yoshizawa et al [5] illustrated that one potential method for increasing the load range of HCCI engines is to operate at late combustion phasings, which can be achieved in recompression HCCI by retaining smaller amounts of exhaust in the cylinder [6], [7]. However, Wagner et al [8] showed that cyclic variations in indicated mean effective pressure (IMEP) grow significantly as the retained exhaust ratio is reduced, and Shahbakhti et al [9] found that cyclic variation in the start of combustion timing increased under similar conditions.…”
Section: Introductionmentioning
confidence: 98%
“…Despite the aforementioned benefits, the upper load limit of the SI-CAI hybrid combustion is still limited due to the unacceptable maximum pressure rise rate (PRRmax) at some loading conditions with homogenous in-cylinder mixture [9]. Retarding the combustion phasing can reduce PRRmax; however, it can increase cyclic combustion variations [9,15,16] as a retarded combustion is not robust enough to accommodate cycle-to-cycle variations of in-cylinder conditions [17]. In addition, an over-retarded combustion phasing would also lead to fuel penalty.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results from Chen et al [21] indicated that the maximum cyclic combustion variation occurs in the initial heat release phase, as measured by the crank angle of 10% accumulated heat release (CA10) at 1500 rpm and 6 bar IMEP. Hellstrom et al [22] and Yoshizawa et al [17] suggested that the cyclic coupling of in-cylinder states, such as the thermal energy and unburned fuel, is the main cause [22] of combustion variation. Those findings indicated the potential for stabilizing the SI-CAI hybrid combustion by enhancing the initial flame propagation process.…”
Section: Introductionmentioning
confidence: 99%